Vaccines against human papillomavirus - Galdos Kajatt, Oscar (2018)
Infection by the human papillomavirus (HPV) is the main factor of cervical cancer. There are currently three vaccines showing efficacy and safety. In Peru, the Ministry of Health has a program of free vaccination for girls aged 9 to 13 years with two doses of tetravalent vaccine (0 and 6 months), whose national coverage is extremely important to reverse the high morbidity and mortality occurring in our country. Older women and boys since age nine can also be vaccinated on their own. This is the main primary prevention that currently exists and must be complemented with secondary prevention.